Social policy review 29 analysis and debate in social policy, 2017 - Hudson, John 1972-; Needham, Catherine 1974-; Heins, Elke ca. 20./21. Jh (Policy Press, 2017)
Published in association with the SPA, this edition presents an up-to-date and diverse review of the best in social policy scholarship over the past twelve months, from a group of internationally renowned authors